Psicologia da saúde e prática psicológica hospitalar: Representações sociais e repercussões na atuação profissional - Santos, Izak Alves dos (2020)
This dissertation was written in article format, according to the model approved by the Graduate Program in Health Psychology at the State University of Paraíba. It concerns a research whose general objective was to analyze the social representations about Health Psychology elaborated by psychologists working in hospitals. It is based on discussions involving Hospital Psychology versus Psychology in the Hospital Context, Health Psychology and Theory of Social Representations. The instruments were a mixed questionnaire, a semi structured interview, and a field journal. The data were analyzed by using descriptive statistics and the enunciation analysis. The results point to a predominantly female sample, with professional careers in offices, hospitals and services of the Unified Social Assistance System (Sistema Único de Assistência Social). The professionals worked an on-call schedule, used different theoretical perspectives, and most identified themselves as a psychologist instead of as a hospital psychologist. In relation to psychological practices, there was an advance in the understanding of activities and interventions concerning hospital practices, highlighting the perception that traditional clinical conduct needs to be reformulated. However, in the field of Social Representations, it is believed that psychologists are still unable to envision, with clarity, a performance aligned with Health Psychology. Most likely, their social representations were anchored in Hospital Psychology with a clinical aspect closely linked to hospital demands. Professional practice, therefore, was aimed at brief psychotherapy, at the preference for a defined therapeutic setting, at the difficulties in managing childhood illness, as well as the centrality of communication and verbal interaction with patients. In conclusion, the study points to the need for systematic training of professionals, from the perspective of Health Psychology with emphasis on psychological performance in contexts of pediatric wards and intensive care units. It is expected that this research will generate new studies aiming to deepen the knowledge of professional practices in other services in public health.